2019
DOI: 10.1371/journal.pone.0222871
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of r-met-hu G-CSF on male reproductive function and development in prepubertal domestic mammals

Abstract: The understanding of mammalian spermatogenesis niche factors active during sexual development may be leveraged to impact reproduction in farm animals. The aim of this study was to evaluate the effects of r-met-hu/G-CSF (filgrastim) on prepubertal sexual development of guinea pigs (Cavia porcellus) and ram lambs (Ovis aries). Individuals of both species were administered r-met-hu/G-CSF daily for 4 days. During and after administration protocols, testicular function and development were assessed through hematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
3
1
Order By: Relevance
“…Thus, the seminal ROS level can be used as an indicator for male infertility ( Agarwal et al, 2006 , Muratoğlu et al, 2018 ). In the current study, suppression in the testosterone concentrations was observed in the Filgrastim-treated rats in comparison with the Control Group and this disagrees with Aponte et al (2019) that reported that the level of testosterone level was unaltered in Guinea pig and increased in ram lambs after administration with G-CSF. FSH and LH level in the two treated groups were significantly higher than in the Control Group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the seminal ROS level can be used as an indicator for male infertility ( Agarwal et al, 2006 , Muratoğlu et al, 2018 ). In the current study, suppression in the testosterone concentrations was observed in the Filgrastim-treated rats in comparison with the Control Group and this disagrees with Aponte et al (2019) that reported that the level of testosterone level was unaltered in Guinea pig and increased in ram lambs after administration with G-CSF. FSH and LH level in the two treated groups were significantly higher than in the Control Group.…”
Section: Discussioncontrasting
confidence: 99%
“…FSH and LH level in the two treated groups were significantly higher than in the Control Group. A study by Aponte et al (2019) reported the elevation of LH level and unchangeable of FSH level in guinea pig while both FSH and LH are increment in ram lambs.…”
Section: Discussionmentioning
confidence: 98%
“…However, in this work, only a few r‐met‐hu G‐CSF‐treated animals had advanced‐to‐elongated spermatids at the end of experiments, suggesting that, although non‐conclusively, r‐met‐hu G‐CSF to some extent may increase the rate of GC differentiation in prepubertal bulls. Previously, our group found a faster progression of GCs during prepubertal development in rams treated with recombinant‐human‐G‐CSF but not in guinea pigs (Aponte et al., 2019), maybe because rams and bulls are ruminants sharing similar reproductive temporal windows in contrast to male guinea pigs, which achieve sexual maturity at approximately 2–3 months (Aponte et al., 2019). The fact that rams and Bos indicus bulls share similar testicular cell kinetics during the prepubertal period in response to the drug may indicate a higher specificity of the human‐targeted drug to ruminant testicular receptors.…”
Section: Discussionmentioning
confidence: 92%
“…However, we found non‐significant differences between the control and treated animals regarding blood parameters, probably due to the limited number of animals used or other unexplained reasons. Bone marrow mobilization occurs after r‐met‐hu G‐CSF administration in a laboratory (guinea pig, Cavia porcellus ) and a farm (rams, Ovis aries ) animal (Aponte et al., 2019).…”
Section: Discussionmentioning
confidence: 99%